1987
DOI: 10.1017/s0022149x00009937
|View full text |Cite
|
Sign up to set email alerts
|

Development, growth and migration of Philophthalmus gralli (Trematoda) from Jordan in the eyes of chicks

Abstract: The growth of Philophthalmus gralli from jordan was studied experimentally by inoculating 10 excysted metacercariae around the right eye of 47 day-old chicks. The growth rate was slow in the first three days during which flukes did not exceed 0·30 mm long. Then growth become rapid reaching 2·70 mm long on day 24. This was followed by a low growth rate during which the flukes grew from 2·70 mm to 2·90 mm on day 40. The flukes started to appear in the left eye on the day 12 post-inoculation of metacercariae in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…This adult worm produced after obtaining on Philophthlamus cercaria from C. bulimoides snail and encysted metacercariae and experimental infection in ducks. This worm species have a mean length of 4.365mm and its detailed morphological features come in agreement with the previous description of corresponding species by, Ismail and Issa (1987), Swarnakumari and Madhavi (1992), Colgan and Nollen (1977) and Radev et al (2000). This worm species has special zoonotic importance where Lamothe-Argumedo et al The most interesting result of the present study is the success in obtaining Philophthalamus species adult worm.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This adult worm produced after obtaining on Philophthlamus cercaria from C. bulimoides snail and encysted metacercariae and experimental infection in ducks. This worm species have a mean length of 4.365mm and its detailed morphological features come in agreement with the previous description of corresponding species by, Ismail and Issa (1987), Swarnakumari and Madhavi (1992), Colgan and Nollen (1977) and Radev et al (2000). This worm species has special zoonotic importance where Lamothe-Argumedo et al The most interesting result of the present study is the success in obtaining Philophthalamus species adult worm.…”
Section: Resultssupporting
confidence: 91%
“…The cercariae encysted directly to form encysted metacercaria, when infect chicks experimentally at one day old by pipetting in the eye, they develop after 35 days post infection to obtain the adult P. hegeneri and P. megalurus from eyes (Colgan and Nollen, 1977). Ismail and Issa, 1987in Jordan, Swarnakumari and Madhavi, 1992in India, Radev et al, 2000and Diaz et al, 2002 Venzuela, they recorded that the snail Melanoides tuberculata was the intermediate host for P. gralli, P. nocturnes and P. species. They found that the snail emerged naturally cercariae which directly encysted.…”
mentioning
confidence: 99%
“…The growth characteristics of adult flukes are in agreement with other digeneans studied, in which three phases are usually recognised: the lag-phase, the rapid phase and the stationary phase (Fried, 1962;Nollen, 1971;Nollen & Murray, 1978;Ismail & Issa, 1987). In P. orientalis the lag-phase lasted for 5 days after which it entered a rapid phase that continued for the rest of the period studied (35 days).…”
Section: Discussionsupporting
confidence: 86%
“…Most of the early investigations on the growth of digeneans pertain to the growth of adult flukes from metacercariae either in experimental hosts or in culture media (Fried, 1962;Nollen, 1971;Harris et al, 1972;Hong, 1982;Franco et al, 1986 andIsmail &Issa, 1987). A few investigations have also been undertaken on the growth of metacercariae from cercariae in the intermediate host (Benjamin & James, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Emerged cercariae encysted within 40-60 seconds. Encysted metacercariae were excysted by their placement in saline at 37C° for several minutes (Ismail and Issa, 1987a). These excysted metacercariae were subsequently used to infect chicks.…”
Section: Snails Collectionmentioning
confidence: 99%